Mutations in SRD5B1 (AKR1D1), the gene encoding Δ(4)-3-oxosteroid 5β-reductase, in hepatitis and liver failure in infancy - Lemonde, H A (Copyright 2003 by Gut, 2003)
Background: A substantial group of patients with cholestatic liver disease in infancy excrete, as the major urinary bile acids, the glycine and taurine conjugates of 7α-hydroxy-3-oxo-4-cholenoic acid and 7α,12α-dihydroxy-3-oxo-4-cholenoic acid. It has been proposed that some (but not all) of these have mutations in the gene encoding Δ(4)-3-oxosteroid 5β-reductase (SRD5B1; AKR1D1, OMIM 604741). Aims: Our aim was to identify mutations in the SRD5B1 gene in patients in whom chenodeoxycholic acid and cholic acid were absent or present at low concentrations in plasma and urine, as these seemed strong candidates for genetic 5β-reductase deficiency. Patients and subjects: We studied three patients with neonatal onset cholestatic liver disease and normal γ-glutamyl transpeptidase in whom 3-oxo-Δ(4) bile acids were the major bile acids in urine and plasma and saturated bile acids were at low concentration or undetectable. Any base changes detected in SRD5B1 were sought in the parents and siblings and in 50 ethnically matched control subjects. Methods: DNA was extracted from blood and the nine exons of SRD5B1 were amplified and sequenced. Restriction enzymes were used to screen the DNA of parents, siblings, and controls. Results: Mutations in the SRD5B1 gene were identified in all three children. Patient MS was homozygous for a missense mutation (662 C>T) causing a Pro198Leu amino acid substitution; patient BH was homozygous for a single base deletion (511 delT) causing a frame shift and a premature stop codon in exon 5; and patient RM was homozygous for a missense mutation (385 C>T) causing a Leu106Phe amino acid substitution. All had liver biopsies showing a giant cell hepatitis; in two, prominent extramedullary haemopoiesis was noted. MS was cured by treatment with chenodeoxycholic acid and cholic acid; BH showed initial improvement but then deteriorated and required liver transplantation; RM had advanced liver disease when treatment was started and also progressed to liver failure. Conclusions: Analysis of blood samples for SRD5B1 mutations can be used to diagnose genetic 5β-reductase deficiency and distinguish these patients from those who have another cause of 3-oxo-Δ(4) bile aciduria, for example, severe liver damage. Patients with genetic 5β-reductase deficiency may respond well to treatment with chenodeoxycholic acid and cholic acid if liver disease is not too advanced.